Follow‐up of post‐transplant minimal residual disease and chimerism in childhood lymphoblastic leukaemia: 90 d to react. (19th December 2014) - Pochon, Cécile; Oger, Emmanuel; Michel, Gérard; Dalle, Jean‐Hugues; Salmon, Alexandra; Nelken, Brigitte; Bertrand, Yves; Cavé, Hélène; Cayuela, Jean‐Michel; Grardel, Nathalie; Macintyre, Elizabeth; Margueritte, Geneviève; et al.
Summary Relapse after transplantation is a major cause of treatment failure in paediatric acute lymphoblastic leukaemia (ALL). Here, we report the findings of a prospective national study designed to investigate the feasibility of immune intervention in children in first or subsequent remission following myeloablative conditioning. This study included 133 children who received a transplant for ALL between 2005 and 2008. Minimal Residual Disease (MRD) based on T cell receptor/immunoglobulin gene rearrangements was measured on days −30, 30, 90 and 150 post‐transplantation. Ciclosporin treatment was rapidly discontinued and donor lymphocyte infusions (DLI) were programmed for patients with a pre‐ or post‐transplant MRD status ≥10−3. Only nine patients received DLI. Pre‐ and post‐transplant MRD status, and the duration of ciclosporin were independently associated with 5‐year overall survival (OS), which was 62·07% for the whole cohort. OS was substantially higher in patients cleared of MRD than in those with persistent MRD (52·3% vs. 14·3%, respectively). Only pre‐transplant MRD status (Hazard Ratio 2·57, P = 0·04) and duration of ciclosporin treatment (P < 0·001) were independently associated with relapse. The kinetics of chimerism were not useful for predicting relapse, whereas MRD monitoring up to 90 d post‐transplantation was a valuable prognostic tool to guide therapeutic intervention.